A Survey on Vehicular Ad-Hoc Networks Routing Protocols: Classification and Challenges- - TASSOULT Nadia; AMAD Mourad; MOUMEN Hamouma; KALLA Hamoudi (Journal of Digital Information Management, 2019)
The Vehicle ad hoc Networks (VANET) are attracting more and more manufacturers and researchers’ attention. Many challenges must be addressed before VANETs can be successfully deployed. The most challenging issue in VANETs is designing of routing mechanisms and efficient medium access control protocols so that safety related and other application messages can be timely and reliably disseminated through VANETs. The aim of VANET routing protocols is establishing of an efficient route between network nodes that should adapt to the rapid changes in the network topology. However, routing protocols in VANET is a challenging issue, mainly due to the rapidly changing topology of vehicles and frequent fragmentation in the network. In this work, we review the most frequent routing protocols for VANETs and then we provide a taxonomy of these protocols based on the used relay selection technique. We compare and discuss these routing protocols according to different criteria. Moreover, we discuss several issues and prerequisite that should be considered when designing VANETs routing. Finally, we highlight the most important aspects and future directions that could be explored in the design of a new Geocast routing solution for vehicular routing algorithms as a contribution for further work.